LEGAL PROTECTION OF CUSTODY RIGHTS FOR DUAL CITIZENSHIP CHILDREN AFTER THE DISSOLUTION OF MARRIAGE - Wicaksana, Agus Arief; Astutik, Sri; Prawesthi, Wahyu; Hartoyo (Awang Long Law Review, 2024)
The purpose of this research is first to determine the legal consequences of the breakup of mixed marriage on the custody of dual citizenship children and second, to understand the judge's considerations in handing down a decision as legal protection of child custody after the breakup of mixed marriage normative legal research methods. In the era of growing globalization, population mobility between countries has become increasingly common. This often causes mixed marriages between Indonesian citizens and foreigners to occur. Obstacles for people carrying out marriages of different nationalities, both within and outside the country, are regarding legal protection for children if in a marriage in Indonesia, for example, there is a divorce which has an impact on the division of assets, child custody, and so on. The most prominent impact of this kind of marriage is the birth of children with dual citizenship or dual citizenship. These children are citizens of more than one country at birth, and this presents unique challenges regarding their custody when parents divorce. An issue that is vulnerable and often arises in mixed marriages is the issue of the child's citizenship. Even though there are several legal regulations governing child custody, disputes over child custody often become disputes in court that require fair handling by judges. In this research, the judge decided that custody of a dual-citizen child would be given to the biological mother by applying the principle of the best interests of the child.